An in-depth exploration of recent advances and promising 20 outlooks in biogas production - Rodrigues, Antônio Felipe da Silva (2023)
RODRIGUES, Antonio Felipe da Silva. An in-depth exploration of recent advances and promising 20 outlooks in biogas production. 2023. 89f. Dissertação - Curso de Mestrado Acadêmico em Energia e Ambiente, Instituto de Engenharias e Desenvolvimento Sustentável, Universidade da Integração Internacional da Lusofonia Afro-Brasileira, Redenção-Ceará, 2023.